Uncoupling Protein 2 and Peroxisome Proliferator-Activated Receptor γ Gene Polymorphisms in Association with Diabetes Susceptibility in Chinese Han Population with Variant Glucose Tolerance - Meicen Zhou; Shuli He; Fan Ping; Wei Li; Lixin Zhu; Xiangli Cui; Linbo Feng; Xuefeng Zhao; Huabing Zhang; Yuxiu Li; Qi Sun (International Journal of Endocrinology)
Objective. To investigate the association of polymorphisms in uncoupling protein 2 (UCP2) and peroxisome proliferator-activated receptor (PPARγ) with glucolipid metabolism in Chinese Han population. Methods. Five hundred eighty-nine subjects were divided into normal glucose tolerance (NGT) group (n=198) and abnormal glucose tolerance group (n=358). HbA1c, blood lipid profile, plasma glucose, and insulin were determined. Insulin sensitivity (HOMA-IR and Matsuda index (ISIM)) and insulin secretion indexes (HOMA-β, early and total phase disposition index) were evaluated. Eight potential functional SNPs in UCP2 and 7 in PPARγ were selected. SNPs were genotyped on Sequenom MassARRAY platform. Results. The GG genotype of rs2920502 in PPARγ was associated with decreased risk of impaired glucose tolerance (G allele: OR: 0.818, 95%CI: 0.526–0.969, P=0.042; GG: OR: 0.715, 95%CI: 0.527–0.97, P=0.031). The TT genotype of rs3856806 in PPARγ was associated with increased risk of impaired glucose tolerance (T allele: OR: 1.46, 95%CI: 1.055–2.017, P=0.022; TT: OR: 1.58, 95%CI: 1.104–2.761, P=0.032). The GG genotype of rs2920502 in PPARγ had better blood glucose and increased insulin secretion and had lower HOMA-IR than GC/CC genotypes. Conclusion. It probably could prevent insulin resistance in early stage by classifying the genotype of rs649446 and rs7109266 in UCP2. The GG genotype of rs2920502 in PPARγ had a decreased risk for diabetes. The TT genotype of rs3856806 in PPARγ had an increased risk for diabetes.